Study on Lightning Intruding Overvoltage in Yantan Extension Substation - Tao Hong Zeng; Lin Lin Lin; Xin Zhi Wang; Gang Wen Tian; Cong Feng; Huai Zhi Xiao (Institute of Advanced Engineering and Science, 2014)
500kV substation is especially important to the grid of our country, once it encounters lightning damage, the safety and reliability of the whole power system will be directly affected. As lightning intruding waves will cause overvoltage on electric equipments by intruding from the transmission line or straightly stroking the substation, which seriously influences the insulation level of equipments, so it is essential to calculate overvoltage on electric equipments when substation struck by lightning to ensure their safe operation under the protection of arrester. As for the new connection mode of extension project of Yantan 500kV substation, numerical model of hydropower equipments is established and electromagnetic transient simulation calculation software of ATP/EMTP is used for calculation of overvoltage on electric equipments. According to the result, conclusions about strong insulating of incoming line towers, importance of lightning shielding failure intruding waves and influence of power frequency voltage on lightning intruding overvoltage in 500 kV substation can be drawn. This is the first-time study on overvoltage in 500kV substation extension project and has certain practical guidance. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4796